Astrocytes expressing mutant SOD1 and TDP43 trigger motoneuron death that is mediated via sodium channels and nitroxidative stress - Rojas, Fabiola; Cortes, Nicole; Abarzua, Sebastian; Dyrda, Agnieszka; Van Zundert, Brigitte A. (Frontiers in Cellular Neuroscience, 2014)
Amyotrophic lateral sclerosis (ALS) is a fatal paralytic disorder caused by dysfunction and degeneration of motor neurons. Multiple disease-causing mutations, including in the genes for SOD1 and TDP-43, have been identified in ALS. Astrocytes expressing mutant SOD1 are strongly implicated in the pathogenesis of ALS: we have shown that media conditioned by astrocytes carrying mutant SOD1G93A contains toxic factor(s) that kill motoneurons by activating voltage-sensitive sodium (Nav) channels. In contrast, a recent study suggests that astrocytes expressing mutated TDP43 contribute to ALS pathology, but do so via cell-autonomous processes and lack non-cell-autonomous toxicity. Here we investigate whether astrocytes that express diverse ALS-causing mutations release toxic factor(s) that induce motoneuron death, and if so, whether they do so via a common pathogenic pathway. We exposed primary cultures of wild-type spinal cord cells to conditioned medium derived from astrocytes (ACM) that express SOD1 (ACM-SOD1G93A and ACM-SOD1G86R) or TDP43 (ACM-TDP43A315T) mutants; we show that such exposure rapidly (within 30-60 minutes) increases dichlorofluorescein (DCF) fluorescence (indicative of nitroxidative stress) and leads to extensive motoneuron-specific death within a few days. Co-application of the diverse ACMs with anti-oxidants Trolox or esculetin (but not with resveratrol) strongly improves motoneuron survival. We also find that co-incubation of the cultures in the ACMs with Nav channel blockers (including mexiletine, spermidine or riluzole) prevents both intracellular nitroxidative stress and motoneuron death. Together, our data document that two completely unrelated ALS models lead to the death of motoneuron via non-cell-autonomous processes, and show that astrocytes expressing mutations in SOD1 and TDP43 trigger such cell death through a common pathogenic pathway that involves nitroxidative stress, induced at least in part by Nav channel activity.